2009
DOI: 10.1242/jeb.030684
|View full text |Cite
|
Sign up to set email alerts
|

Passive maintenance of high angle of attack and its lift generation during flapping translation in crane fly wing

Abstract: SUMMARYWe have studied the passive maintenance of high angle of attack and its lift generation during the crane fly's flapping translation using a dynamically scaled model. Since the wing and the surrounding fluid interact with each other, the dynamic similarity between the model flight and actual insect flight was measured using not only the non-dimensional numbers for the fluid (the Reynolds and Strouhal numbers) but also those for the fluid-structure interaction (the mass and Cauchy numbers). A difference w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 29 publications
5
90
0
Order By: Relevance
“…It has been, for example, shown that wing deformations [13,14] can enhance the force generation and efficiency of a locust operating at Re % 4 Â 10 3 [13], or a hawkmoth at Re % 6.3 Â 10 3 [15]. Moreover, several studies have suggested that insect wing rotations may be passive [16,17], meaning that the resulting rotation is due to a dynamic balance between the wing inertial force, elastic restoring force and fluid dynamic force.…”
Section: Introductionmentioning
confidence: 99%
“…It has been, for example, shown that wing deformations [13,14] can enhance the force generation and efficiency of a locust operating at Re % 4 Â 10 3 [13], or a hawkmoth at Re % 6.3 Â 10 3 [15]. Moreover, several studies have suggested that insect wing rotations may be passive [16,17], meaning that the resulting rotation is due to a dynamic balance between the wing inertial force, elastic restoring force and fluid dynamic force.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, other insects usually have small Reynolds number. The Reynolds number is from 100 to 200 for Drosophila melanogaster [27] , around 333 for Crane fly [28] , from 1200 to 3000 for Bumblebee [29] , around 1140 for dragonfly [13] , and from 250 to 500 for smallest dragonfly [30] . There were 53 frames for a single stroke, which means that the duration of one cycle (T) lasted 0.027 s and that the frequency (f) was (37.7 ± 0.3) Hz.…”
Section: Resultsmentioning
confidence: 99%
“…In a series of experimental studies, chordwise and spanwise flexibility have been shown to increase propulsive efficiency in flapping-based propulsion [4][5][6]. In the works by Ishihara et al [7] and Zhao et al [8], a dynamically scaled mechanical model of flapping flight was used to measure the aerodynamic forces on flapping wings of variable flexural stiffness. Due to the complexity of fluid-structure interaction (FSI) problems, in computational simulations simplifications are usually made, either in the model for the fluid or for the structure.…”
Section: Introductionmentioning
confidence: 99%